El procedimiento especial sancionador en el sistema electoral mexicano - Olmeda Garcìa, Marina del Pilar (2013)
This article portrays a critical review on the Special Sanctioning Procedure as an administrative, legal, political and electoral, political procedure in Mexico, on the political parties for administrative electoral authorities of federate institutions, on the Federal Electoral Institute and citizens in order to investigate, suspend and sanction violations to the rules of election propaganda, whether on the press, radio or television. It also analyzes the misuse of public resources allocated to public servants, which aims at preserving the different electoral process steps by the enforcement of sanctioning electoral regulations, with the ultimate goal of conducting the electoral process in a fair and legal manner, to thus fulfill the sovereign mandate to elect the people’s representatives, which contributes to the country’s political, social and economic stability.